Rational Emotive Behavior Therapy (REBT) Approach in Improving Anger Emotion Regulation in Adolescents with a Family History of Bipolar Disorder - Naomi Athina; Sri Redatin Retno Pudjiati (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Early adolescence is a critical period for emotional and cognitive development, often accompanied by emotional turbulence due to hormonal and neurodevelopmental changes. Adolescents with a family history of bipolar disorder are at a higher risk of experiencing emotional regulation problems. This study aims to explore the effectiveness of Rational Emotive Behavior Therapy (REBT) in improving emotion regulation abilities in a female adolescent with a familial risk of bipolar disorder. A single-subject design (N=1) with pre-test and post-test measurements was employed. The participant was a 14-year-old girl with difficulties regulating anger and a father diagnosed with bipolar disorder. The REBT intervention comprised 5 sessions, with 1 pre-intervention session, and 1 follow-up session. Emotion regulation was measured using the Emotion Regulation Questionnaire-Child Adolescent (ERQ-CA) and the PROMIS Emotional Distress—Calibrated Anger Measure. Results indicated a significant increase in the use of cognitive reappraisal strategies and a decrease in expressive suppression strategies following the REBT intervention. The participant’s anger expression decreased from severe to mild categories. A shift from irrational beliefs to rational beliefs was also observed, supporting improved emotion regulation abilities. This study supports the effectiveness of REBT in enhancing emotion regulation in adolescents with a familial risk of bipolar disorder. REBT helped the participant better manage anger, highlighting its potential as an effective intervention strategy for addressing emotion regulation issues in at-risk adolescents. These findings have important implications for clinical practice and the development of interventions for at-risk adolescent populations.Masa remaja awal adalah periode krusial dalam perkembangan emosional dan kognitif yang seringkali diiringi oleh turbulensi emosi akibat perubahan hormonal dan neurodevelopmental. Remaja dengan riwayat keluarga bipolar berisiko lebih tinggi mengalami masalah regulasi emosi. Penelitian ini bertujuan mengeksplorasi efektivitas Rational Emotive Behavior Therapy (REBT) dalam meningkatkan kemampuan regulasi emosi remaja perempuan dengan faktor risiko keluarga bipolar. Penelitian ini menggunakan desain single subject (N=1) dengan pengukuran pre-test dan post-test. Partisipan adalah seorang remaja perempuan berusia 14 tahun dengan kesulitan meregulasi emosi marah dan memiliki ayah dengan gangguan bipolar. Intervensi REBT dilakukan dalam 5 sesi, beserta satu sesi pra intervensi, dan satu sesi follow up. Pengukuran regulasi emosi dilakukan menggunakan Emotion Regulation Questionnaire-Child Adolescent (ERQ-CA) dan PROMIS Emotional Distress—Calibrated Anger Measure. Hasil penelitian menunjukkan peningkatan signifikan dalam penggunaan strategi regulasi emosi cognitive reappraisal dan penurunan penggunaan strategi expressive suppression setelah intervensi REBT. Ekspresi emosi marah partisipan menurun dari kategori severe ke mild. Perubahan pemikiran dari irrational belief ke rational belief juga teramati, mendukung peningkatan kemampuan regulasi emosi. Penelitian ini mendukung efektivitas REBT dalam meningkatkan regulasi emosi pada remaja dengan risiko keluarga bipolar. REBT membantu partisipan mengelola emosi marah dengan lebih baik. Intervensi ini berpotensi menjadi strategi efektif dalam menangani masalah regulasi emosi pada remaja, terutama dalam konteks keluarga dengan riwayat bipolar. Temuan ini memberikan implikasi penting bagi praktik klinis dan pengembangan intervensi untuk populasi remaja berisiko.